Cost-efficiency improvement of bivalves shells preparation when tracing their geographic origin through ICP-MS analysis of elemental fingerprints. (December 2020) - Ricardo, Fernando; Mamede, Renato; Bispo, Regina; Santos, Andreia; Ferreira da Silva, Eduardo; Patinha, Carla; Calado, Ricardo
Abstract: Developing methodologies employed to trace the geographic origin of seafood as accurate and fast as possible can help to speed-up the delivery of results to legal authorities, reduce associated costs and minimize environmental impacts (associated with the residues generated). The present study evaluated if trace element fingerprints (TEF) of a small homogenized subsample of Manila clams ( Ruditapes philippinarum ) right valve yielded a representative elemental signature of the whole shell. Four elemental ratios (Ba/Ca, Mg/Ca, Mn/Ca and Sr/Ca) commonly employed to trace the geographic origin of bivalves were determined from subsamples of 0.2 and 3 g of the homogenized right valve and the whole left valve (4 g). A Canonical Analysis of Principal Coordinates developed for the subsamples of small portions (0.2 g) of the homogenized right valve revealed an accuracy of 100%, that led to the correct classification of the subsample of 3 g to their respective valve and that of 4 g to its matching shell. Results achieved indicate that TEF of a small homogenized portion of a bivalves valve is representative of the whole shell and can be employed to provide an accurate, fast, reliable and environmentally safer method to trace its geographic origin. Highlights: Trace element fingerprints can be used to trace the geographic origin of bivalves. A small portion of one valve can be used as a reliable proxy of the whole shell. This approach makes ICP-MS analysis more environmentally friendly. This approach is faster and equally reliable for traceability of geographic origin.